2012
DOI: 10.1182/blood-2011-09-378414
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective multicenter analysis of elderly Hodgkin lymphoma: outcomes and prognostic factors in the modern era

Abstract: We investigated a recent (January 1999 to December 2009) cohort of 95 elderly Hodgkin lymphoma subjects. At diagnosis, median age was 67 years (range, 60-89 years), whereas 61% had significant comorbidity, 26% were unfit, 17% had a geriatric syndrome, and 13% had loss of activities of daily living. Overall response rate to therapy was 85%, whereas incidence of bleomycin lung toxicity was 32% (with associated mortality rate, 25%). With 66-month median follow-up, 2-year and 5-year overall survival were 73% and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
122
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 23 publications
13
122
1
Order By: Relevance
“…No pulmonary AEs $ grade 3 were reported, whereas Evens et al 7 reported a 32% incidence of bleomycin lung toxicity (with an associated mortality rate of 25%) among 95 patients, 70% of whom were treated with ABVD. Stamatoullas et al 33 reported a 27% incidence of bleomycin lung toxicity (20% early; 7% late) among 147 ABVD-treated patients, leading the investigators to propose a reduction or omission of bleomycin from the regimen; 29% of deaths in that study were due to toxicity, including 14% due to pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…No pulmonary AEs $ grade 3 were reported, whereas Evens et al 7 reported a 32% incidence of bleomycin lung toxicity (with an associated mortality rate of 25%) among 95 patients, 70% of whom were treated with ABVD. Stamatoullas et al 33 reported a 27% incidence of bleomycin lung toxicity (20% early; 7% late) among 147 ABVD-treated patients, leading the investigators to propose a reduction or omission of bleomycin from the regimen; 29% of deaths in that study were due to toxicity, including 14% due to pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Evens et al reported an ORR of 85% in 95 patients, 70% of whom received ABVD, 7 and an ORR of 68% in 44 patients treated with ABVD or Stanford V in approximately equal proportions. 8 Similarly, Stamatoullas et al reported an 84% ORR in 147 older HL patients treated with ABVD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corticosteroids are the usual treatment, with some evidence of improvement [19]. In a recent retrospective multicenter analysis of the elderly HL by Evens et al [20], an incidence of bleomycin lung toxicity (BLT) of 32% was observed, with an associated mortality rate of 25%; these data supported the association of BLT and risk factors such as older age, cumulative bleomycin dose, renal insufficiency, pulmonary radiation, underlying lung disease, and tobacco history, and the concomitant use of G-CSF (the incidence of BLT was 38% and 0% among pts receiving G-CSF versus patients who did not receive it, resp.) [21].…”
Section: Lung Diseasesmentioning
confidence: 99%